ANALYSIS OF AUTHENTICITY OF TEACHERSâ MADE ASSESSMENT AND ITS CONTRIBUTION TO STUDENTSâ ENGLISH ACHIEVEMENT IN ELEMENTARY SCHOOLS IN BULELENG REGENCY - Natalia, S. A. M. K. D.; Marhaeni, A.A.I.N; Dantes, N. (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at analyzing and investigating the authenticity of teacherâs made assessment and its contribution to studentsâ English achievement in Elementary schools in Buleleng regency. The authenticity of teachersâ made assessment was seen in terms of teachersâ assessment planning, assessment implementation as perceived by teachers, teachersâ assessment implementation as perceived by students. This study was also intended in order to know the contribution of those aspects to studentsâ English achievement. The research design for this study was Exploratory Mix-Method design, involving 33 English teachers. The data were collected through documentation, and questionnaires which were analyzed qualitatively and quantitatively. The result of data analysis showed that teachersâ assessment planning, assessment implementation as perceived by teachers and students had sufficient level of authenticity. From statistical analysis, it was found that only teachersâ assessment planning and assessment implementation as perceived by students which had significant contribution to studentsâ English achievement. However, it was also found that the three aspects were integratedly gave significant contribution to studentsâ English achievement. In conclusion, it showed how the teachersâ assessments with its level of authenticity gave contribution to the studentsâ English achievement. Â Keywords: teachersâ assessment authenticity, studentsâ achievement